Caregivers in the family: Daughters, sons and social norms - Francesca Barigozzi; Helmuth Cremer; Kerstin Roeder (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2017)
Daughters are the principal caregivers of their dependent parents. In this paper, we study long-term care (LTC) choices by bargaining families with mixed- or same-gender siblings. LTC care can be provided either informally by children, or formally at home or in an institution. A social norm implies that daughters su¤er a psychological cost when they provide less informal care than the average child. We show that the laissez-faire (LF) and the utilitarian first-best (FB) di¤er for two reasons. First, because informal care imposes a negative externality on daughters via the social norm, too much informal care is provided in LF. Second, the weights children and parents have in the family bargaining problem might differ in general from their weights in social welfare. We show that the FB allocation can be achieved through a system of subsidies on formal home and institutional care. Except when children and parents have equal bargaining weights these subsidies are gender-specific and reffect Pigouvian as well as "paternalistic" considerations.
Keywords: D13; H23; H31; I19; 330; Social norms; formal and informal LTC; daughters; sons